Tantangan dan Strategi Menghadapi Perubahan Kurikulum di Sekolah - Deasy Yunita Siregar; Nurul Fadhilah; Khairunnisa Khairunnisa; Lailatul Fitria; Putri Fadhila Batubara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is to explore the challenges and strategies in dealing with curriculum change at the school level. We will analyze the various factors that can influence the acceptance and implementation of curriculum change. This research is motivated by the existence of curriculum change at the school level, which in its implementation is often faced with complex challenges. So it is necessary for schools to know, then analyze these challenges that are likely to arise. After that, it is necessary for schools and educators to create and carry out effective strategies to overcome these challenges. This research uses a literature study research method in which the data collected and analyzed are secondary data derived from research results such as books, articles, journals, internet sites, and others relevant to this research. The conclusion in this study is that curriculum changes in schools bring many challenges for teachers and students. Challenges and strategies in dealing with curriculum changes in schools can be understood through the theoretical basis of change management and learning theory. Effective strategies are needed to overcome complex challenges in implementing curriculum change in schools.